Performance of Cypermethrin, Deltamethrin and Nimbicidine on Larval Development of Tribolium castaneum (Herbst) - Khatun, R; Islam, W; Mondal, KAMSH (Journal of Bio-Science, 2011)
Context: Pyrethroid insecticides and natural products individually or in mixture can protect stored products by retarded growth and delayed larval period. Objectives: To investigate the effects of cypermethrin, deltamethrin and azadirachtin either alone or in combinations on the larval development of Tribolium castaneum (Herbst). Materials and Methods: T. castaneum larvae were reared in flour medium treated with cypermethrin, deltamethrin and nimbicidine alone and in combinations. Ten newly hatched larvae were placed in a petri dish (4cm diam) containing 1g of either fresh or treated flour and kept in an incubator (30 ± 0.5°C). The larvae were regularly observed for pupation and the larval period was noted. The weights of the fourth and sixth instar larvae were taken on an electric balance. Twenty larvae from each age were weighed for different treatments. Results: The larval period was 36.25 days in the treatment of combined cypermethrin, deltamethrin and nimbicidine. Both cypermethrin (20.55 days) and deltamethrin (20.38 days) failed to prolong the larval period significantly (P>0.05) in comparison with that control (19.68 days). In nimbicidine the average larval period was 30.38 days. Larval weight was significantly (P<0.05) reduced by nimbicidine alone and in combination with cypermethrin and deltamethrin in comparison with that of control. In control the average weight of 9 days old larvae was 188.60 mg. The lowest larval weight was 75.50 mg when nimbicidine was combined with cypermethrin and deltamethrin. In nimbicidine alone it was 84.25 mg. The average weight of 16 days old larvae in control was 2142.75 ± 62.67 mg with the lowest being 1955.05 mg in the treatment of combined cypermethrin, deltamethrin and nimbicidine. Conclusion: Azadirachtin either alone or in combination with pyrethroid insecticides viz., cypermethrin and delatmethrin may reduce T. castaneum larval development and thus shows excellent protection of stored products. Key words: Cypermethrin; Deltamethrin; Nimbicidine; Larvae; Growth; Development; Tribolium DOI: 10.3329/jbs.v17i0.7100 J. bio-sci. 17: 45-50, 2009